2010
DOI: 10.1080/14786410802265084
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane glycoside from Hemidesmus indicus as a potential anti-oxidant and anti-dyslipidemic agent

Abstract: A new pregnane glycoside hindicusine (1) was isolated from the CHCl(3)-EtOH (3 : 2) extract of Hemidesmus indicus, whose structure was established on the basis of spectroscopic studies. The glycoside (1) and its acetylated derivative (5) were evaluated for their anti-oxidant and anti-dyslipidemic activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The active principles of Hemidesmus indicus, 2-hydroxy 4-methoxy benzoic acid and pregnane glycoside, showed antihyperlipidaemic and antidyslipidemic effects [180, 181]. …”
Section: Introductionmentioning
confidence: 99%
“…The active principles of Hemidesmus indicus, 2-hydroxy 4-methoxy benzoic acid and pregnane glycoside, showed antihyperlipidaemic and antidyslipidemic effects [180, 181]. …”
Section: Introductionmentioning
confidence: 99%
“…We reported earlier that some precursors in hormone synthesis, such as, guggulsterone, possess lipid-lowering activity, together with mild anti-oxidant effect and also inhibit oxidative modification of LDL [6]. Recently, we also found that some pregnane derivatives exhibited antioxidant and anti-dyslipidemic activities simultaneously [7,8].…”
Section: Introductionmentioning
confidence: 83%
“…Animals, which were acclimatized for one week before starting the experiment, had free access to normal diet and water ad libitum [7,8] …”
Section: Experimental Animalsmentioning
confidence: 99%
“…Chatterjee and Bhattacharya, 1955;Das and Devaraj, 2007;2008 Glycosides Hindicusine, hemidesmosides A-C Anti-adhesive, antioxidant and anti-dyslipidemic. Das and Devaraj, 2006b;Sethi et al, 2010;Zhao et al, in press Tannins Unspecified Mucoprotective, antidiarrhoeal. Kostova, 2005 Aliphatic acids Dodecanoic acid, hexadecanoic acid, linalyl acetate, dihydrocarvyl acetate, hexatriacontane The aqueous extract, 100 mg/kg, administered prior to bromobenzene, showed significant beneficial effects including respiratory stimulation, prevention of the rise in lipid peroxides and protein carbonyls, and increased the level of sulphydryl groups back to control levels.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%